The rise of metallurgy in Eurasia : evolution, organisation and consumption of early metal in the Balkans - Radivojević, Miljana,; Roberts, Benjamin W.,; Marić, Miroslav,; Kuzmanović Cvetković, Julka,; Rehren, Thilo, (Archaeopress Archaeology, 2021)
'The Rise of Metallurgy in Eurasia' is a landmark study in the evolution of early metallurgy in the Balkans. It demonstrates that far from being a rare and elite practice, the earliest metallurgy in the world was a common and communal craft activity.